Chemical vapor deposition of ruthenium-based layers by a single-source approach. Issue 12 (3rd March 2016) - Jeschke, Janine; Möckel, Stefan; Korb, Marcus; Rüffer, Tobias; Assim, Khaybar; Melzer, Marcel; Herwig, Gordon; Georgi, Colin; Schulz, Stefan E.; Lang, Heinrich
Abstract : Single-source precursors Ru(CO)2 (P( n -Bu)3 )2 (O2 CR)2 allow the successful deposition of Ru(P) layers by the CVD process. Abstract : A series of ruthenium complexes of the general type Ru(CO)2 (P( n -Bu)3 )2 (O2 CR)2 (4a, R = Me;4b, R = Et;4c, R = i-Pr;4d, R = t -Bu;4e, R = CH2 OCH3 ;4f, R = CF3 ;4g, R = CF2 CF3 ) was synthesized by a single-step reaction of Ru3 (CO)12 with P( n -Bu)3 and the respective carboxylic acid. The molecular structures of4b, 4c and4e–g in the solid state are discussed. All ruthenium complexes are stable against air and moisture and possess low melting points. The physical properties including the vapor pressure can be adjusted by modification of the carboxylate ligands. The chemical vapor deposition of ruthenium precursors4a–f was carried out in a vertical cold-wall CVD reactor at substrate temperatures between 350 and 400 °C in a nitrogen atmosphere. These experiments show that all precursors are well suited for the deposition of phosphorus-doped ruthenium layers without addition of any reactive gas or an additional phosphorus source. In the films, phosphorus contents between 11 and 16 mol% were determined by XPS analysis. The obtained layers possess thicknesses between 25 and 65 nm and are highly conformal and dense as proven by SEM and AFM studies.